Anatomical variation of the spinous and transverse processes in the caudal cervical vertebrae and the first thoracic vertebra in horses. (11th February 2015) - Santinelli, I.; Beccati, F.; Arcelli, R.; Pepe, M.
Summary: Reasons for performing study: There are scant data on the incidence of different anatomical variants of the equine caudal cervical spine, despite interest in cervical pathology. Objectives: To identify morphological radiographic variation in the 6th and 7th cervical vertebrae and the first thoracic vertebra in horses of different breeds and to determine whether there are breed‐ and sex‐related differences. Study design: Retrospective descriptive study. Methods: Radiographs of the cervical spine of 270 horses were assessed retrospectively. The Chi‐square test, or Fisher's exact test when appropriate, was used to test for associations between radiographic findings and sex or breed, and residual analysis was performed to localise differences. Chi‐square tests and calculation of phi coefficient (φ) were used to test for associations between different types of radiological variation. Results: Three variants were identified in the spinous process of the 7th cervical vertebra, and 2 variants were identified in the spinous process of the first thoracic vertebra. The presence of the spinous process of the 7th cervical vertebra was associated with breed, and transposition of the ventral process of the 6th cervical vertebra onto the ventral aspect of the 7th cervical vertebra was associated with sex. The shape of the spinous process of first thoracic vertebra was associated with the shape of the spinous process of the 7th cervical vertebra and with the presence of transposition of the ventral process of the 6th cervical vertebra onto the ventral aspect of the 7th. Conclusions: A large number of anatomical variants can be detected radiographically in the caudal cervical area; some of these have a higher frequency, depending on sex and breed. Knowledge of the different shapes is very important in avoiding misdiagnosis of periarticular new bone formation. The spinous process of the first thoracic vertebra has 2 morphological variants.